Role of Testosterone in Pediatric Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
To elucidate the male preponderance in pediatric stroke, researchers at University of Munster, Germany, Hospital for Sick Children Toronto, Canada, and other centers measured total testosterone in 72 children with arterial ischemic stroke (AIS), 52 with cerebral sinovenous thrombosis (CSVT), and in 109 healthy controls.